Manajemen Kesiswaan Untuk Pengembangan Diri Peserta Didik - Amin, Muhammad; Andriani, Tuti; Afandi, Muslim (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
This study aims to determine; 1) student management at MAN 1 Pekanbaru, student self-development at MAN 1 Pekanbaru, 2) student self-development at MAN 1 Pekanbaru, 3) Student management for student self-development carried out at MAN 1 Pekanbaru, 4) supporting factors and inhibition of student management for self-development of students at MAN 1 Pekanbaru. This type of research is a field research with a qualitative research method approach and using descriptive data analysis. Data collection was done by interview, observation and documentation. Data analysis technique using data reduction), data display and conclusion drawing/verification. Based on the results of this study indicate that: 1) Student management carried out at MAN 1 Pekanbaru has been running in accordance with the concept of student management, 2) Self-development of students carried out by MAN 1 Pekanbaru has been running in accordance with aspects of self-management, 3) Student management for the self-development of students carried out MAN 1 Pekanbaru has been running in accordance with management functions, 4) The supporting factors for student management for self-development of students are: (a) Professional and competent mentor teachers, (b) Motivation of participants very strong students, (c) adequate facilities and infrastructure, (d) solid cooperation between teams. While the inhibiting factors are: (a) The budget for activities is not maximized, (b) Cooperation with government agencies is still minimal, (c) News publications about school have not been organized